2020
DOI: 10.1007/s40615-020-00820-9
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for Healthcare Providers Managing COVID-19 in Rural and Underserved Areas

Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has ravaged many urban and high-density areas in the USA. However, rural areas (despite their low population density) may be especially vulnerable to poor outcomes from COVID-19, owing to limited healthcare infrastructure, long distances to advanced health care, and population characteristics (e.g., high tobacco use, hypertension, obesity, older age). A panel of experts who are actively engaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The population living in rural areas has more chronic diseases than the urban population 23 , which is a possible factor that justifies a higher risk of COVID-19-related mortality in rural and peri-urban areas. Moreover, living in rural areas decreases ICU admission, probably because of the lack of ICU care in the public health service in the region 24 . Previous studies have shown a rapid increase in COVID-19, with greater dispersion in the interior and rural areas, increasing the need for care within this population 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The population living in rural areas has more chronic diseases than the urban population 23 , which is a possible factor that justifies a higher risk of COVID-19-related mortality in rural and peri-urban areas. Moreover, living in rural areas decreases ICU admission, probably because of the lack of ICU care in the public health service in the region 24 . Previous studies have shown a rapid increase in COVID-19, with greater dispersion in the interior and rural areas, increasing the need for care within this population 25 .…”
Section: Discussionmentioning
confidence: 99%
“… 9 These factors could compound the disparities that already exist between rural citizens and those who live elsewhere due to the higher prevalence of high-risk populations, and less access to transportation, the internet, healthcare, and mental health services in rural settings. 10 , 11 Addressing these health disparities needs to be a priority to minimize morbidity and mortality among rural citizens. In addition, it is imperative to address the misconceptions and inaccurate beliefs about COVID-19 transmission heard by IPs in this study in order to increase compliance with public health safeguards among rural community members.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive infection control can affect the conditions of nursing homes, especially in rural settings with scant healthcare resources [ 21 , 22 ]. Infection control requires limiting medical care in medical facilities and reducing the duration of care provided to patients, which can lead to low-quality medical care and the risk of missing signs of acute conditions in patients [ 23 , 24 , 25 ]. Additionally, as few healthcare resources are available in nursing homes in rural areas, the staff cannot take a day off if they are symptomatic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%